Investigating the relationship between determinants of employee wellbeing and innovation: a policy and practice perspective - Dediu, Vlad (2021)
The European Union (EU) 2020 Strategy was the broad EU agenda for growth and jobs, aimed at promoting socio-economic development and productivity. An important consideration within this was the negative impact that the 2008 crisis had, which was compounded by the less than optimal response observed in many organisations. It became clear that the path to a competitive economy was achievable only through sustainable practices that do not overlook the health and wellbeing (WB) of the workforce. The concept of innovation has received increased attention, as it promised to offer a potential way forward. Within the area of employment and work, two concepts emerged that were of relevance to the broader idea of innovation: workplace innovation (WI) and innovative work behaviours (IWB). However, much more work was needed to clearly understand how to develop truly holistic frameworks for innovation and WB.